Taxonomic reinvestigation of Favolus in the Neotropics utilizing morphological and multigene phylogenetic analyses - Zabin, Denis Augusto; Spirin, Viacheslav; Vlasák, Josef; Coelho-Nascimento, Cristiano; Menolli, Nelson (Mycological progress, 2024)
Favolus is a genus of white-rot polypores with a worldwide distribution, characterized by laterally attached, fleshy to flexible basidiomata, and mostly large, radially elongated pores. The generic type, Favolus brasiliensis , originally described from Brazil, has been recently suggested as a species complex based on DNA data. Additionally, new species have been described based on morphological and molecular data without, however, addressing potential earlier available names. Thus, a thorough revision of type specimens of the Neotropical taxa currently associated with Favolus ( Polyporus ) tenuiculus was conducted. Further morphological studies and multigene (ITS, nucLSU, TEF1 , and RPB1 ) phylogenetic analyses of the newly collected Favolus specimens from the Atlantic Forest of Brazil and other localities in the Neotropics were carried out. In total, 127 new sequences (62 ITS, 30 nucLSU, 22 TEF1 , and 13 RPB1 ) of Favolus species were generated. GenBank sequences of two type specimens incorporated in our analyses clarified the phylogenetic position of F. elongoporus , a species previously described from Brazil, and proved a new combination in Favolus for Polyporus laetiporoides , a recently described species from Costa Rica. In contrast to the previous phylogenetic studies that recognized two supported clades among F. brasiliensis sequences as two probable species, the present study advocates for a broader concept as a single species. Moreover, we select a lectotype and a new epitype for F. brasiliensis and discuss its identity versus P. tenuiculus . Morphological studies and molecular data of new collections and older type specimens support the recovery of Favolus reniformis and Hexagonia rhombipora as distinct species of Favolus . Additionally, F. tessellatus, F. trigonus and F. pseudoprinceps are justified as older names for the recently described F. rugulosus , F. radiatifibrillosus and F. yanomamii , respectively. Detailed morphological descriptions of the collections and pure cultures obtained for this study are provided, along with comments, illustrations, and a key for species of Favolus from the Neotropics.